Vitamin C-related nutrient–nutrient and nutrient–gene interactions that modify folate status - Lucock, Mark; Yates, Zoë; Boyd, Lyndell; Naylor, Charlotte; Choi, Jeong-Hwa; Ng, Xiaowei; Skinner, Virginia; Wai, Ron; Kho, Jeremy; Tang, Sa; Roach, Paul; Veysey, Martin (European journal of nutrition, 2013)
Purpose Folate-related nutrient–nutrient and nutrient–gene interactions modify disease risk; we therefore examined synergistic relationships between dietary folic acid, vitamin C and variant folate genes with respect to red cell folate status. Methods Two hundred and twelve subjects were examined using chemiluminescent immunoassay, PCR and food frequency questionnaire to determine red cell and serum folate, 14 folate gene polymorphisms, dietary folate (natural and synthetic) and vitamin C. Results When examined independently, synthetic PteGlu correlates best with red cell folate at higher levels of intake ( p = 0.0102), while natural 5CH 3 -H 4 -PteGlu n correlates best with red cell folate at lower levels of intake ( p = 0.0035). However, dietary vitamin C and 5CH 3 -H 4 -PteGlu n interact synergistically to correlate with red cell folate at higher levels of intake ( p = 0.0005). No interaction between dietary vitamin C and PteGlu was observed. This ‘natural’ nutrient–nutrient interaction may provide an alternative to synthetic PteGlu supplementation that is now linked to adverse phenomena/health outcomes. On its own, vitamin C also correlates with red cell folate ( p = 0.0150) and is strongly influenced by genetic variation in TS, MTHFR and MSR, genes critical for DNA and methionine biosynthesis that underpin erythropoiesis. Similarly, dietary vitamin C and 5CH 3 -H 4 -PteGlu n act synergistically to modify red cell folate status according to variation in folate genes: of note, heterozygosity for 2R3R-TS ( p = 0.0181), SHMT ( p = 0.0046) and all three MTHFR SNPs ( p = 0.0023, 0.0015 and 0.0239 for G1793A, C677T and A1298C variants, respectively) promote a significant association with red cell folate. Again, all these genes are critical for nucleic acid biosynthesis. Folate variants with the strongest independent effect on folate status were C677T-MTHFR ( p = 0.0004) and G1793A-MTHFR ( p = 0.0173). Conclusions 5CH 3 -H 4 -PteGlu n assimilation and variant folate gene expression products may be critically dependent on dietary vitamin C.